THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON BUSINESS GROWTH: THE MEDIATING ROLE OF BUSINESS PERFORMANCE - Franz Jun Harbin; Fahrul Riza (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
This study examines the relationship between entrepreneurial orientation and business growth with the mediating role of sustainable and market performance in food and beverage of micro and small businesses. The study developed and empirically tested a structural model using data collected from the micro and small business entrepreneurs responsible for the day-to-day operations of the business located in Tangerang city and its surrounding area. The results show that entrepreneurial orientation positively affects business growth in emerging markets. Further, sustainability and market performance partially mediated the indirect relationship between entrepreneurial orientation and business growth. This study makes a novel contribution to the entrepreneurial orientation and business performance literature as it finds evidence that business performance is an effective way to transmit the firm's entrepreneurial orientation into business performance and to support the growth of micro and small firm assets. To grow, micro and small business managers need to have a proactive, innovative and risk-taking attitude in running a business. In addition, for businesses to have positive and consistent growth, business managers need to monitor business sustainability performance and market performance.